Algorithmic Approach to Anterolateral Thigh Flaps Lacking Suitable Perforators in Lower Extremity Reconstruction. Issue 5 (May 2015) - Lu, Johnny Chuieng-Yi; Zelken, Jonathan; Hsu, Chung-Chen; Chang, Nai-Jen; Lin, Chih-Hung; Wei, Fu-Chan; Lin, Cheng-Hung
<x xml:space="preserve">Abstract</x> Background: The anterolateral thigh flap is preferred at the authors' institution for lower extremity reconstruction. When variations in vascular anatomy preclude flap harvest, the authors follow an algorithm for contingency planning. The authors compared outcomes of contingency strategies to anterolateral thigh flaps that go as planned. Methods: Between January of 2001 and February of 2012, 548 free anterolateral thigh flaps were planned for lower extremity reconstruction at Chang Gung Memorial Hospital. In 30 cases, the flap could not be used because perforators were not identified (n = 12), unreliably small (n = 14), or injured (n = 4). Using the authors' algorithm, the flap was converted to an ipsilateral tensor fasciae latae (n = 21), anteromedial thigh (n = 5), or contralateral vastus lateralis myocutaneous flap (n = 4). Outcomes, including flap failure, necrosis, and re-exploration rate, were compared in successful cases and those that required conversion. Results: The incidence of unreliably small or absent perforators was 4.8 percent. Adding cases of iatrogenic perforator injury, the incidence was 5.5 percent. There was no difference in flap survival, flap loss, or need for re-exploration regardless of whether or not the anterolateral thigh flap was used. In 70 percent of cases, the authors favored the tensor fasciae latae flap; partial flap necrosis occurred in six of 21 cases, and total flap loss occurred in one. Conclusions: Without preoperative imaging, dilemmas may be encountered in roughly one of 20 anterolateral thigh flaps raised. Using the authors' algorithm, alternative options can reliably confer results comparable to those of planned anterolateral thigh flaps. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.